Analysis of Public Administration Comparison Among Provinces in Indonesia: Challenges and Opportunities - A. Muhammad Fadli Mappisabbi; Nurasia Natsir (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This study aims to analyze the comparison of public administration across various provinces in Indonesia. Utilizing a mixed-methods approach that combines both qualitative and quantitative research methods, this research investigates the unique challenges faced by public administration in each province and explores the opportunities for improvement. The findings reveal that cultural, economic, and political factors significantly influence the effectiveness of public administration, leading to variations in service delivery, accountability, and citizen engagement. Moreover, the study highlights the importance of regional context in shaping administrative practices and outcomes. Based on these insights, the study provides targeted recommendations for enhancing the performance of public administration at the provincial level, emphasizing the need for tailored strategies that consider local conditions and stakeholder involvement. Ultimately, this research contributes to a deeper understanding of public administration dynamics in Indonesia and offers a foundation for future studies in this field.